2010
DOI: 10.2337/db10-0688
|View full text |Cite
|
Sign up to set email alerts
|

First-Trimester Prediction of Gestational Diabetes Mellitus: Examining the Potential of Combining Maternal Characteristics and Laboratory Measures

Abstract: OBJECTIVEPredictors of gestational diabetes mellitus (GDM) have been widely studied, but few studies have considered multiple measures. Our objective was to integrate several potential GDM predictors with consideration to both simple and novel measures and to determine the extent to which GDM can be predicted in the first trimester.RESEARCH DESIGN AND METHODSWe identified first-trimester maternal samples from 124 women who developed GDM and 248 control subjects who did not. We gathered data on age, BMI, parity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
139
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(153 citation statements)
references
References 22 publications
10
139
1
3
Order By: Relevance
“…Many other studies [3,7,[12][13][14] supported similar finding. In fact, one of the studies gave strong recommendation that algorithms derived from multiple regression analysis of maternal characteristics and obstetric history can potentially identify about 60 % pregnancy that will develop GDM [13].…”
Section: Discussionsupporting
confidence: 67%
“…Many other studies [3,7,[12][13][14] supported similar finding. In fact, one of the studies gave strong recommendation that algorithms derived from multiple regression analysis of maternal characteristics and obstetric history can potentially identify about 60 % pregnancy that will develop GDM [13].…”
Section: Discussionsupporting
confidence: 67%
“…Savvidou et al have demonstrated that several biochemical measurements in the first trimester of pregnancy can improve the discrimination of high-and low-risk individuals, in addition to simple anamnestic variables using the WHO criteria for diagnosing GDM [34]. However, inclusion of some novel risk variables did not improve test accuracy in our analysis; therefore, and to optimise the cost-effectiveness of the algorithm, these biochemical variables were not included in our prediction model, which was primarily based on cheap and simple variables that are ubiquitously available in an obstetric setting.…”
Section: Discussionmentioning
confidence: 99%
“…Disentangling the effect of maternal obesity per se from that of maternal diabetes on maternal metabolism and pregnancy outcomes in the women with obesity and diabetes in pregnancy is almost impossible without very large cohorts with refined metabolic measures. In observational studies and larger population cohort studies in normal pregnancy, increasing maternal triglycerides in early pregnancy have been associated with increased rates of preeclampsia (4,5), future diagnosis of GDM (17,23), induced preterm delivery (5), and LGA infants (5). Low maternal HDL-C in early pregnancy has also been associated with increased risk of later GDM (23), and elevated HDL-C has been associated with lower rates of preterm birth (24).…”
Section: Maternal Obesitymentioning
confidence: 99%
“…In observational studies and larger population cohort studies in normal pregnancy, increasing maternal triglycerides in early pregnancy have been associated with increased rates of preeclampsia (4,5), future diagnosis of GDM (17,23), induced preterm delivery (5), and LGA infants (5). Low maternal HDL-C in early pregnancy has also been associated with increased risk of later GDM (23), and elevated HDL-C has been associated with lower rates of preterm birth (24). Both low (,10th centile) and high (.90th centile) maternal total cholesterol have been associated with preterm birth (6,25), with one study showing a trend to increased rates of microcephaly for low (,10th centile) maternal cholesterol (25) ( Table 2).…”
Section: Maternal Obesitymentioning
confidence: 99%